KOMPETENSI SDM KEUANGAN DAN AKUNTABILITAS PESANTREN - Yunika Murdayanti; Dita Puruwita (Politeknik Negeri Batam, 2019)
Financial management of pesantren is not so complicated, because pesantren are self-financing institutions that do not require financial accountability to be reported to the funder. Generally, this study discusses about the competence of financial human resources against accountability in the environment of Pesantren (Islamic Education Institution). Observations conducted by researchers on financial management in 6 Pesantren at Jabodetabek. Its population is all employees who are in pesantren. The sample was selected using purposive sampling amounted to 116 respondents. The data analysis method uses regression testing. Conclusion of this study proves that the competence of financial human resources have a positive and significant impact on accountability. The higher of the financial human resources will have an effect on the implementation of accountability at pesantren well and adequate.